A time-varying geometry modeling method for parts with deformation during machining process. (April 2020) - Hao, Xiaozhong; Li, Yingguang; Cheng, Yinghao; Liu, Changqing; Xu, Ke; Tang, Kai
Highlights: A time-varying geometry modeling method for parts with deformation is proposed. In-process measurement and cutting simulation are incorporated based on a novel modeling method. The geometric representation model is constructed based on a curved surface mapping approach. Only a small amount of measurement data is needed for modeling the actual deformed geometry. The accuracy of the reconstructed model is sufficient for process analysis and adjustment. Abstract: Deformation due to residual stress is a significant issue during the machining of thin-walled parts with low rigidity. If there are multiple processes with deformation during machining, some process suitability issues will appear. On this occasion, the actual geometric state of the deformed workpiece is needed for process adjustment. However, it is still a challenge to obtain the complete geometry information of deformed workpiece accurately and efficiently. In order to address this issue, a time-varying geometry modeling method, combining cutting simulation and in-process measurement, is proposed in this paper. The deformed workpiece model can be reconstructed via transforming the deformed workpiece with only a small amount of the measurement points by superimposing material removal and workpiece deformation simulation according to a time sequence, which takes advantage of the proposed Curved Surface Mapping based Geometric Representation Model ( CSMGRM ). Machining experiment of a typical structural part has shown that the deformed geometry model of the whole workpiece can be reconstructed within the error of 0.05mm, which is less than one tenth of the finish machining allowance in general cases, and it is sufficient to meet the accuracy requirements for interference or overcut/undercut analysis and process adjustment.